Estimation of Electric Vehicle Market in Malaysia by using Euler’s Method and Runge-Kutta Method - Mohamad, Ahmad Danial; Mohamad, Mahathir (Enhanced Knowledge in Sciences and Technology, 2025)
This study investigates the growth of Malaysia’s electric vehicle (EV) market using numerical methods to enhance forecasting accuracy, crucial for informed decision-making by stakeholders. Existing methods like Euler’s Method often result in significant inaccuracies over long-term predictions due to their simplicity. To address this, the study employs both Euler’s Method and the more advanced Runge-Kutta Fourth Order (RK4) Method, utilizing MATLAB simulations to compare their accuracy and in modelling exponential market growth. By analysing Malaysia’s EV market dynamics and validating these numerical approaches, the research provides improved predictive tools for manufacturers, policymakers, and investors. The findings aim to support strategic planning and the broader transition toward sustainable transportation solutions. In this study, the EV market growth is modelled using an exponential growth equation, which is solved using numerical methods such as Euler’s Method and the Runge-Kutta Fourth Order (RK4) Method. The study confirms that the Runge-Kutta Fourth Order (RK4) method significantly outperforms Euler’s Method in forecasting the growth of Malaysia’s EV market. RK4 provides higher accuracy and, particularly for long-term predictions.